1997
DOI: 10.1021/jp972099a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mixing in Binary Surfactant Solutions by Surface Tension and Neutron Reflection:  Anionic/Nonionic and Zwitterionic/Nonionic Mixtures

Abstract: Surface tension and neutron reflection measurements have been used to study the surface composition of aqueous solutions of mixtures of sodium dodecyl sulfate (SDS) and n-dodecyl--D-maltoside (C 12 maltoside) and C 12 maltoside and n-dodecyl-N,N′-dimethylamino betaine (C 12 betaine). From measurements of surface tension and mixed critical micelle concentrations (cmc) the pseudo-phase separation model has been used to calculate values of the interaction parameters in the micelle, M , and at the surface, σ . SDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
168
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(195 citation statements)
references
References 43 publications
(69 reference statements)
27
168
0
Order By: Relevance
“…C 10 M has a considerably smaller maximum concentration at the air/water interface max , than C 10 G. This may be due to the inability of the planar air/water interface to accommodate the larger hydrophilic head in C 10 M. Since the reduction of the surface tension of the solvent is a function of the values of max and the CMC/C 20 ratio (as shown by Eq. [7]) (6d), [7] this accounts for the considerably lower γ cmc of C 10 G than C 10 M. An increase in the pH from 5.7 to 9 does not have much effect on the surface properties of C 10 M, C 10 G, and C 12 M. However, with change in pH, C 12 TMAC showed a decrease in the value of the CMC as well as in the area/molecule, which may be due to the compression of the electric double layer around the hydrophlic head with an increase in the electrolyte content at the higher pH. Table 2 shows the surface properties of the surfactant mixtures.…”
Section: Surface Properties Of the Individual Surfactantsmentioning
confidence: 95%
See 1 more Smart Citation
“…C 10 M has a considerably smaller maximum concentration at the air/water interface max , than C 10 G. This may be due to the inability of the planar air/water interface to accommodate the larger hydrophilic head in C 10 M. Since the reduction of the surface tension of the solvent is a function of the values of max and the CMC/C 20 ratio (as shown by Eq. [7]) (6d), [7] this accounts for the considerably lower γ cmc of C 10 G than C 10 M. An increase in the pH from 5.7 to 9 does not have much effect on the surface properties of C 10 M, C 10 G, and C 12 M. However, with change in pH, C 12 TMAC showed a decrease in the value of the CMC as well as in the area/molecule, which may be due to the compression of the electric double layer around the hydrophlic head with an increase in the electrolyte content at the higher pH. Table 2 shows the surface properties of the surfactant mixtures.…”
Section: Surface Properties Of the Individual Surfactantsmentioning
confidence: 95%
“…Although there are some papers that deal with surfactant mixtures containing alkylglycosides (7)(8)(9)(10) in terms of the surface properties, they only show the C 20 (surfactant concentration in the aqueous phase required to reduce the surface tension of the solvent by 20 mN m −1 ) and/or CMC values for the individual components and the mixtures, and in almost all cases the measurements were done in the absence of the swamping amount of electrolyte required to ensure that the β values are accurate.…”
Section: Introductionmentioning
confidence: 99%
“…The ± sign in Eqs. [8] and [9] reflects the phase uncertainty arising from Eq. [1], and in practice this does not present a problem for such systems.…”
Section: (2) Structure Of the Mixed C 16 Tab/phenyl Ethanol Monolayermentioning
confidence: 99%
“…For example, the surface composition and mixed micelle concentration has been investigated for ndodecyl-β-D-maltoside and sodium dodecyl sulfate (SDS) and n-dodecyl-N ,N -dimethylamino betaine respectively, using surface tension and neutron reflection measurements (7). It was shown that the maltoside surfactant interacts strongly with the SDS micelles rendering a net attraction between the surfactants.…”
Section: Introductionmentioning
confidence: 99%